Liver injury after methylprednisolone pulses: A disputable cause of hepatotoxicity. A case series and literature review. Issue 6 (1st July 2019) - Zoubek, Miguel Eugenio; Pinazo-Bandera, José; Ortega-Alonso, Aida; Hernández, Nelia; Crespo, Javier; Contreras, Fernando; Medina-Cáliz, Inmaculada; Sanabria-Cabrera, Judith; Sanjuan-Jiménez, Rocío; González-Jiménez, Andrés; García-Cortés, Miren; Lucena, M Isabel; et al.
Abstract : Background and Objectives: Corticosteroids are often empirically used to treat idiosyncratic hepatotoxicity with severe features. Interestingly, intravenous methylprednisolone (MP) is increasingly being recognized as being responsible for liver injury. We aimed to characterize MP‐induced liver injury by analyzing demographical, clinical, laboratory and outcome data of three MP‐induced hepatotoxicity cases and compared this information with that of previously published cases. Case series: Three females with multiple sclerosis (MS) were treated intravenously with MP, mean daily dose 767 mg. Liver damage occurred 2 to 6 weeks after exposure. Severity was mild to moderate. Two patients suffered positive rechallenge. Literature review: We identified 50 published cases of MP hepatotoxicity. Most of these cases were female (86%) and main treatment indications were MS (29 cases) and Graves' ophthalmopathy (13 cases). Hepatocellular damage predominated and mean time to onset was 6 weeks. Four patients died and rechallenge occurred in 19 cases. Conclusion: MP pulses can induce severe liver injury, often with an autoimmune phenotype, particularly in patients with MS and Graves' ophthalmopathy. Consequently, these patient groups should have liver tests monitored when treated with MP to provide safer patient care.